Amine-based CO2 capture sorbents: A potential CO2 hydrogenation catalyst. (July 2018) - Chakravartula Srivatsa, Srikanth; Bhattacharya, Sankar
Graphical abstract: Highlights: CO2 adsorption mechanism on amine-based sorbents was discussed. Highlights the effect of CO2 concentration and amine loading of adsorbed species. Highlights solid amine sorbents as probable CO2 hydrogenation catalysts. Abstract: Mechanism of CO2 adsorption on amine loaded SBA-15 sorbents with varying amine coverage has been assessed using thermogravimetric analysis (TGA) and in-situ Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS). TGA study showed that sorbent adsorption capacities increased by 122–153% with CO2 concentrations (5–80%) in the gas at 50/75 °C. The DRIFTS studies indicate that low amine loaded sorbents exhibit higher uptakes with an increase in CO2 concentrations which is attributed to the mode of CO2 adsorption i.e. 1:1 CO2 to amine forming carbamic acid. At higher amine loadings CO2 is adsorbed following the 1:2 CO2 to amine forming carbamate-ammonium ions pair resulting in lower adsorption capacities per amine site. The studies also showed an increase in carbamic acid formation with pressure from 100 to 500 kPa at low amine loadings and both carbamic acid and carbamates at higher amine loadings. The paper provides insights into the mechanistic understanding of CO2 adsorption behaviour of the varyingly covered amines on the SBA-15 support with a change in concentration and pressure of CO2 . The current work presents the conditions to alter the CO2 adsorption mechanism on amine sites with potential application in CO2 conversion to chemicals.